THE ANALYSIS OF TECHNOLOGY ACCEPTANCE MODEL (TAM) ON INTENTION TO USE OF E-MONEY IN MANADO (STUDY ON: GOPAY, OVO, DANA) - Legi, Denada; Saerang, Regina T. (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2020)
Abstract: In this digital era technology has become a part of todayâ€™s people's life, e-money has played an important and central role in the transaction and development of e-money from data 2014-2018 the development of users e-money that always increases, even rather rapidly. The purpose of this study is to find out more about the factors of affecting the intention to use e-money. Four variables used in this research, are Perceived Usefulness, Perceived Ease of Use, Perceived Risk, and Perceived Trust. This study employs multilinear regression to analyze the influence of those variables to intention to use e-money. This study conduct with 100 users of e-money (Gopay, OVO, DANA) in Manado as the respondents. The result of this study showed that Perceived Usefulness and Perceived Risk have no significant influence to Intention to Use e-money, meanwhile Perceived Ease of Use and Perceived Trust have a significant and positive influence on Intention to Use. The applications have to improve their performance and services so that the consumer will feel more secure and more comfortable in making transactions.Keywords:Â E-money, Technology Acceptance Model, Perceived Usefulness, Perceived Ease of Use, Perceived Risk, Perceived Trust, Intention to Use.